Proceedings of the ISES Solar World Congress 2019 2019
DOI: 10.18086/swc.2019.05.02
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Symmetric C-PVT Solar Collector Designs with Vertical Bifacial Receivers

Abstract: Photovoltaic thermal (PVT) solar collectors can be an effective solution for system output improvement. Photovoltaic thermal collectors naturally have a more expensive receiver than simpler photovoltaic or thermal only collectors, therefore making concentration a more appealing solution to achieve cost reduction. However, concentrating systems need careful analysis on the design phase in order to optimize the annual output. In addition, for stationary (non-tracking) collectors, it is critical to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(3 reference statements)
0
0
0
Order By: Relevance
“…The utilization of solar energy has demonstrated significant potential as a viable technology (Panchal et al, 2020). Numerous research has demonstrated that implementing solar photovoltaic thermal may result in substantial energy reduction (Saini et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The utilization of solar energy has demonstrated significant potential as a viable technology (Panchal et al, 2020). Numerous research has demonstrated that implementing solar photovoltaic thermal may result in substantial energy reduction (Saini et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%